IMF Survey, Volume 35, Issue 08. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
Spring Meeting overview; IMFC communique; IMF medium-term strategy; Krueger to resign; World Economic Outlook; Sub-Saharan Africa outlook; Asia outlook; Western Hemisphere outlook; Dealing with scaled-up aid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet